ROLA REFLEKSJI W PROCESIE PRZYGOTOWANIA DO ZAWODU NAUCZYCIELA JĘZYKA OBCEGO - Marciniak, Izabela (Neofilolog, 2019)
The process of foreign language teacher training requires the introduction and development of reflection skills for teaching and work as an educator. That is why the process of teacher training must provide students with the necessary knowledge and practice. This article presents the rationale of the teacher training process at the Institute of German Philology, Adam Mickiewicz University in Poznań, according to the standards for teaching from the years 2004 and 2012. The research described concerns the role of self-reflection in students both during the process of their training as future teachers and in their teaching practice in schools.